Graduates’ information seeking behavior / Maslinda Mohd Nadzir, Juhana Salim and Azizah Jaafar - Salim, Juhana; Jaafar, Azizah; Mohd Nadzir, Maslinda (Faculty of Information Management, 2013)
Past studies on information seeking behaviour among students showed that some students are weak in the process of searching for information. The problem should be resolved as there are students who are not exposed to the knowledge of searching for information. This study emphasizes on information seeking behaviour among graduate students involved in research activities. This paper aims to identify graduates’ information seeking behaviour. Based on past research, factors influencing information seeking behaviour are graduate’s field of study, learning styles and information skills. Thus, information seeking behaviour conceptual framework developed in this study consists of the individual factors that influence information seeking behaviour which comprises of information needs, selection of information sources, methods used to search for information and the use of information. The findings of this study showed that majority of graduate students’ prefer to search for their needed information in electronic environment. Information seeking behaviour patterns among graduate students that has been identified, can be used by system analysts to develop a system which can be used by students in the processes of seeking for information to support their research. The improvement on students’ information seeking behaviour will be able to help in building quality human capital.